Areas of action in vocational training during the digital transformation - Hermann, Ralf [Verfasser]; Kress, Hannelore [Verfasser] (My University, 2019)
"The digitalisation of the workplace is predominantly perceived as a 'designable challenge', which first and foremost offers new opportunities. These consist of potentials for new business models and economic growth, facilitation of work processes, diversified working and learning environments and incentives to make vocational education and training more attractive. However, 'the future of digitalisation' must be designed 'by human beings' and 'with a human dimension'. The required normative framework is set by democratic negotiation, regarding which educational goals - and thus which humane and social development goals - should be served by technical innovation, and how its opportunities should be structured, its risks limited and its consequences managed. In this context, education - and especially vocational education - has more than just a technically determined implementation function that reacts to practical constraints." (Extract from text, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; I 1 Internationale Berufsbildung; Berufsbildung; Digitalisierung; Tätigkeitsmerkmal; Tätigkeitswandel; Substitutionseffekte; Internationale Zusammenarbeit